2020
DOI: 10.1007/s12282-020-01136-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of breast cancer precursor lesions by autofluorescence ductoscopy

Abstract: Purpose Autofluorescence is an image enhancement technique used for the detection of cancer precursor lesions in pulmonary and gastrointestinal endoscopy. This study evaluated the feasibility of addition of autofluorescence to ductoscopy for the detection of intraductal breast cancer precursor lesions. Methods An autofluorescence imaging system, producing real-time computed images combining fluorescence intensities, was coupled to a conventional white light ductoscopy system. Prior to surgery, ductoscopy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
9
0
1
Order By: Relevance
“…Non-invasive diagnostic techniques for identifying malignant tumor cells, monitoring distant metastasis and local recurrence of cancer are improving. In particular, the use of inflammatory markers and autofluorescence to diagnose cancer holds promise (30,72,(74)(75)(76)(77). In addition, red cell distribution width (RdW) value may be applied as a novel inflammatory marker to assess malignant thyroid nodules (74).…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive diagnostic techniques for identifying malignant tumor cells, monitoring distant metastasis and local recurrence of cancer are improving. In particular, the use of inflammatory markers and autofluorescence to diagnose cancer holds promise (30,72,(74)(75)(76)(77). In addition, red cell distribution width (RdW) value may be applied as a novel inflammatory marker to assess malignant thyroid nodules (74).…”
Section: Discussionmentioning
confidence: 99%
“…This technique is already used extensively to help identify pathologies within the airways, larynx, and colon [30][31][32]. Moreover, studies have also shown promising results of (auto) fluorescence for the detection of (pre) cancerous lesions of the breast [33,34]. Consequently, enhanced imaging techniques, such as NBI and (auto) fluorescence, combined with robotic surgery could improve margin determination in patients undergoing breast cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…New techniques in ductoscopy are currently being developed and explored to improve the sensitivity for the detection of (pre)malignant lesions. One of these examples is combining ductoscopy with auto-fluorescence imaging [27][28][29]. This addition to ductoscopy may help to detect precancerous lesions in highrisk breast cancer groups since auto-fluorescence has shown to be effective for the detection of precancerous lesions of epithelial origin (such as oesophageal, lung, bronchial and colon cancers) [48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed the success of ductoscopy in finding the intraductal lesion causing PND before or during duct excision [19][20][21][22][23]. Moreover, it is possible to remove or laser-destruct intraductal lesions causing PND, thereby preventing surgery [18,[24][25][26], and new approaches such as auto-fluorescence ductoscopy may improve the detection of precancerous lesions in patients with high risk of developing cancer [27][28][29]. Despite the increasing relevance of ductoscopy for diagnostic and therapeutic purposes, there are no data available on the impact on the quality of life after ductoscopy.…”
Section: Introductionmentioning
confidence: 99%